Reopening Criminal Cases in Azerbaijan: Legal Framework and Procedural Considerations - Mammadova, Lala (Teisė, 2025)
In modern criminal justice systems, maintaining a balance between legal finality and substantive justice remains a fundamental challenge. While the principle of res judicata ensures stability and legal certainty, mechanisms for reopening finalized criminal cases are essential to correct miscarriages of justice and safeguard human rights. This article examines the legal framework governing the reopening of criminal cases in the Republic of Azerbaijan, with particular emphasis on proceedings based on newly discovered circumstances. Drawing on Chapter LIV of the Azerbaijani Criminal Procedure Code, the study analyzes the substantive and procedural grounds for retrial, including the criteria for newly discovered evidence and institutional decision-making processes. The article further situates Azerbaijan’s retrial mechanism within the context of international human rights law, with specific reference to Article 6 of the European Convention on Human Rights. Several structural and normative deficiencies have been identified, such as the absence of a precise legal definition of newly discovered circumstances and limited procedural safeguards at the preliminary review stage. The paper argues that strengthening retrial procedures is essential for enhancing judicial fairness, accountability, and alignment with the European legal standards.